Cancer immunology of cutaneous melanoma: a systems biology approach - Miranda, Mindy Stephania de Los Angeles Muñoz (2020)
Cutaneous melanoma is a melanocyte skin cancer, and it is one of the most aggressive tumours in humans. It causes a significant number of deaths worldwide, and approximately 1,500 melanoma patients die each year in Brazil. The Gene Expression Omnibus (GEO) repository contains high throughput gene expression data, from different samples of cutaneous melanoma. Systems biology seems to be the best approach to investigate the molecular mechanisms of the immune system in melanoma and could explain the tumour escape, proliferation, and growth in other tissues. We proposed an analysis of omic integration with a systems biology approach on melanoma data available from GEO. We found genes related to immune system communication and melanoma. We used regulatory networks from expressed gene data combining transcription factor, protein-protein interaction, and kinase enrichment analysis, to predict markers of immune-related genes that may act as regulators in melanoma progression. We distinguished the interplay of CD74, in CD14+ cells of melanoma patients, in melanoma patients with BRAF V600E, and also in melanoma cell lines that are resistant to BRAF V600E inhibitors: indicating the presence of this molecule as one of the principal modulators of communication between immune cells and melanoma, along with ENO1, S100A6, SERPINE2, GAPDH, and UBB. All of these genes are involved in the Tumour microenvironment (TME) response to progression and treatments in cutaneous melanoma. We identify TNFAIP3 as having an exclusive role in melanoma in CD14+ and CD8+ cells, suggesting that common transcription factors involved in TNFAIP3 or those related to this gene could be drug design targets in melanoma. We proposed that the FN1 gene is modulated by the BRAF V600E mutation and three genes NQO1, ALDOA, and ATCG1, which could be modulated by BRAF with another mutation or by NRAS G13R mutation in melanoma cell lines. We associated IFNGR2 as a type of receptor for melanoma cells that may interfere with the signalling cascade of metastasis melanoma, and that could explain drug resistance to immunotherapies. We hope that this will reveal new and unappreciated links between the immune system and melanoma progression.